Forces for Change in Mathematics Education: The Case of TIMSS - Macnab, Donald S. (Education Policy Analysis Archives, 2000)
The results of the Third International Study in Mathematics and Science Education (TIMSS) were published in 1996/7. Since that time the participating countries have reacted in a variety of ways to the comparative performance of their students. This article investigates the diverse effects these reactions have had on mathematics curricula and teaching methodologies in a selection of these countries, within the context of a wider analysis of the motivations which determine change in education.